2004
DOI: 10.1002/marc.200400027
|View full text |Cite
|
Sign up to set email alerts
|

Location of the Catalytic Site in Supported Atom Transfer Radical Polymerization

Abstract: Summary: A supported and highly recyclable catalyst complex, CuBr/HMTETA physically adsorbed to silica gel, was used for the ATRP of MMA to elucidate the nature of the catalytic site. In some polymerizations, the reaction solutions were filtered and compared with their unfiltered references for catalytic activity. The filtered systems had high catalyst activity indicating the presence of active catalyst sites in solution. These sites are the primary catalytic contributors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 23 publications
(47 reference statements)
0
48
1
Order By: Relevance
“…[6][7][8][9][10][11][12] Recently, however, we determined and reported that the location of the active catalyst sites using the silica supported and physically adsorbed recyclable catalyst we had developed was not on the support's surface. 13 Rather, we found it to be in solution. Given this, we suspected that the activity of the heterogeneous catalyst being used was high and would therefore allow for significant reductions in the concentration of catalyst used, ideally without affecting the polymerization rates and the control of molecular weight.…”
Section: Introductionmentioning
confidence: 88%
“…[6][7][8][9][10][11][12] Recently, however, we determined and reported that the location of the active catalyst sites using the silica supported and physically adsorbed recyclable catalyst we had developed was not on the support's surface. 13 Rather, we found it to be in solution. Given this, we suspected that the activity of the heterogeneous catalyst being used was high and would therefore allow for significant reductions in the concentration of catalyst used, ideally without affecting the polymerization rates and the control of molecular weight.…”
Section: Introductionmentioning
confidence: 88%
“…One of the potential solutions to this problem is to support the catalyst on a solid that can be separated easily from the polymer solution and can be recycled efficiently. The strategies that have been employed with limited success include the use of supported catalyst systems based on silica, ion‐exchange resins, cross‐linked polystyrene (PS) beads, reversible supported and hybrid catalysts, soluble biphasic, and polymer anchored catalyst systems . The supported catalyst systems are broadly classified into three categories: (a) covalent, (b) physisorption, and (c) biphasic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The covalent strategies often have limited mobility for the catalyst; thereby making the accessibility to the diffusing radicals in the solution extremely difficult. Many research groups, have performed heterogeneous ATRP using covalently supported silica catalyst systems . The polymers obtained from these methods exhibited broad MWD and poor initiator efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of the reported supported ATRP systems, the probability of radicals finding higher oxidation state transition metal at the site of activation on the surface is rather low 2. Thus, the major problem associated with the covalent strategies is the limited mobility of the catalyst, thereby making its accessibility to the fast diffusing radicals in the solution extremely difficult while the physisorption strategies also suffer from extensive leaching problem 17, 18, 21, 25. The biphasic and soluble recoverable catalysts are relatively more efficient than solid‐supported catalysts, but their complex preparation and recovery procedures limit applicability in large scale 6, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…The biphasic and soluble recoverable catalysts are relatively more efficient than solid‐supported catalysts, but their complex preparation and recovery procedures limit applicability in large scale 6, 26, 27. Thus, almost all catalyst immobilization methods produce polymers with moderate to broad molecular weight distributions (MWDs) due to uncontrolled chain growth and termination except those strategies that have some amount of catalyst leaching into the solution 21, 25…”
Section: Introductionmentioning
confidence: 99%